Rancang Bangun Pendeteksi Kertas Struk pada Mesin Anjungan Tunai Mandiri Berbasis Mikrokontroler - Fattah, Muhammad Najihurrahman; Faisal, Faisal; Saputra, Wahyuddin (Journal Software, Hardware and Information Technology, 2023)
Proof of transaction printed by an Anjungan Tunai Mandiri (ATM) generally produces printed electronic information about the amount of money, account for the transaction, location, and transaction time. Article 5 paragraph (1) of Law no.11 of 2008 concerning electronic information and transactions ("UU ITE") Article 5 paragraph (1) of the ITE Law in full reads, "Electronic information and electronic documents and printouts are tools legal proof."In many cases, there is no notification of the amount of paper available; common events occur to customers after transactions at the ATM; proof of transfer or receipt needs to be printed because the paper supply at the ATM has run out. If this happens, the customer must go to the Bank office to print bank statements. This research aims to design a receipt paper detector on a microcontroller-based ATM. In concept, this tool can detect the availability of receipt paper in ATMs and provide notifications when the receipt paper runs out.